Blaustein's pathology of the female genital tract - Kurman, Robert J.; Ronnett, Brigitte M.; Ellenson, Lora Hedrick; SpringerLink (Online service). (New York London Springer, 2010)
Since the publication of the 1/e in 1977, Blaustein's Pathology of the Female Genital Tract has consolidated its position as the leading textbook of gynecological pathology. An essential reference for all pathologists and residents, this thoroughly updated Sixth Edition includes more than 1400 illustrations in color, informative tables and 22 revised chapters written by internationally recognized experts. Discussion of each specific entity is organized to include general information, etiology, and epidemiology followed by clinical features, pathologic findings, differential diagnosis, clinical behavior, and treatment. This clear organization is applied throughout the book and allows the reader to quickly access key information in every chapter. Blaustein's Pathology of the Female Genital Tract remains the gold-standard reference for practicing pathologists and trainees, as well as for obstetric/gynecology practitioners and residents.
Benign diseases of the vulva -- Premalignant and malignant tumors of the vulva -- Diseases of the vagina -- Benign diseases of the cervix -- Precancerous lesions of the cervix -- Carcinoma and other tumors of the cervix -- Benign diseases of the endometrium -- Precursor lesions of endometrial carcinoma -- Endometrial carcinoma -- Mesenchymal tumors of the uterus -- Diseases of the fallopian tube and paratubal region -- Nonneoplastic lesions of the ovary -- Diseases of the peritoneum -- Surface epithelial tumors of the ovary -- Sex cord-stromal, steroid cell, and other ovarian tumors with endocrine, paraendocrine, and paraneoplastic manifestations -- Germ cell tumors of the ovary -- Nonspecific tumors of the ovary, including mesenchymal tumors -- Metastatic tumors of the ovary -- Diseases of the placenta -- Gestational trophoblastic tumors and related tumor-like lesions -- Hematologic neoplasms and selected tumor-like lesions involving the female reproductive organs -- Soft tissue lesions involving female reproductive organs.
Previous ed.: 2002.
Electronic reproduction.
Keywords: Gynecologic pathology; Female urogenital diseases -- Pathology; Genital neoplasms, Female -- Pathology; Electronic books